Ontogenetic changes in the tyrosine hydroxylase immunoreactive preoptic area in the small-spotted catshark Scyliorhinus canicula (L., 1758) females: catecholaminergic involvement in sexual maturation - Porceddu, Riccardo; Porcu, Cristina; Mulas, Giovanna; Spiga, Saturnino; Follesa, Maria Cristina (Frontiers in Neuroanatomy, 2024)
The brain-pituitary-gonadal (BPG) axis plays a crucial role in vertebrates, mediating the influence of environmental and internal cues on the central nervous system and the development of gonads. In BPG axis, the action of catecholaminergic neurons in the brain is a determinant factor, largely unexplored in Chondrichthyes. Among these, catsharks exhibit several characteristics that make them an ideal model for investigation. In our research, we focused on female populations of Scyliorhinus canicula (L., 1758), a reference species for oviparous sharks, which were sampled and grouped at different maturity stages (immature, maturing, mature, mature egg-laying). Our goals were to characterize and assess differences in the somata morphometry and in the number of tyrosine hydroxylase immunoreactive (TH+) neurons in two specific regions: the periventricular preoptic (PO) nucleus, considered a positive control for ovarian development, as well as the suprachiasmatic nucleus (SCN), serving as a negative control. Our qualitative and quantitative study confirmed the presence of two distinct populations of TH+ neurons (TH+ PO and TH+ SCN), providing new insights into this species for the first time. The changes observed in TH+ PO seem to be related to the degree of ovarian maturity whose neurons were more abundant and probably more excitable in the maturing phase. In contrast, changes in the TH+ SCN in S. canicula females were not related to ovarian maturity, but rather to unknown internal or environmental factors. These results provide valuable insights for future research, such as investigating potential connections between TH+ PO neurons and nearby neurons in the preoptic area.